Joint Forest Management in the State of Maharashtra - Mitra, S. K. (Indian Forester, 2000)
Joint Forest Management in a real sense began in Maharashtra from 1996-97 and 58 villages were included in the first instance under this plan. This has now increased to 602 villages. Financial assistance is provided by State Govt. in a phased manner for its various components. The micro-plans are prepared in consultation with the villagers. Total area covered at present is about 2 lakhs ha, under the protection of village committees. Corporate houses are also participating in several of its programmes. The progress is monitored at Circle and State levels. Documentation is done as it is likely to motivate the people. Training is being imported to Forestry staff at different levels. Village level workshops are also organized. Benefits have been noticed in the quality of forest mlmagement, moisture regime and better quality of grasses and some employment to the villagers. Future plans are to extend the scheme to the management of more than 181akhs ha, spread over 10,720 villages in a phased manner. When Govt. assistance shall be stopped, the scheme will be able to sustain itself from the forests' own resources and an initiative has been made by levying some nominal fees, etc. Naxalite infested areas are proposed to be included in the scheme.